Employee Work Discipline at PT. Pegadaian (Persero) Makassar Branch - Ariadi, Aisyah; Arhas, Sitti Hardiyanti; Nasrullah, Muh. (ASHA Publishing, 2025)
This study aims to analyze employee work discipline at PT Pegadaian (Persero) Makassar Branch by identifying the forms of discipline demonstrated, as well as the supporting and inhibiting factors. A qualitative descriptive approach was used, with data collected through interviews, observation, and documentation. The informants included the head of the Warehouse Management Subdivision and General Subdivision staff. The data were analyzed using descriptive analysis and validated through source and technique triangulation to ensure credibility. The findings reveal that employee work discipline is reflected in five key indicators: attendance, responsibility, attitude, compliance with norms, and collateral management. While employees demonstrate good responsibility and positive attitudes in communication and teamwork, several problems remain. Attendance irregularities, such as tardiness and unauthorized absences, are still common. Norm compliance is inconsistent across units, although collateral management procedures are generally well executed. Supporting factors identified include rewards, employee compliance, skills, insight, and challenges provided by management. Conversely, discipline is hindered by environmental influences, indifference to leadership authority, and lack of assertiveness from supervisors. These factors contribute to disciplinary lapses and suggest areas for managerial improvement. This research contributes to the understanding of employee discipline in state-owned enterprises and highlights the need for targeted interventions to improve supervision and internal motivation. The study recommends structured enforcement of rules, stronger leadership assertiveness, and ongoing performance-based rewards to enhance employee discipline at PT Pegadaian.